2021
DOI: 10.3390/ijerph18168736
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parental Education and Physical Activity on the Long-Term Development of the Physical Fitness of Primary School Children: An Observational Study

Abstract: Low physical fitness (PF) has been associated with higher risk of suffering from different diseases. The importance of PF is evident already in early ages, as children’s PF appears to be a key factor of their future PF and physical activity level. Among the variables that may have an influence on children’s PF, the importance of parent’s socioeconomic status and active/inactive behaviors has been stressed in several previous studies. However, previous literature has mostly reported this association through cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Researchers have previously demonstrated that the development of physical fitness is not only influenced by physical activities and sports, but also by factors such as genetics, environment ( 42 ); socioeconomic status of parents ( 43 , 44 ); parental education ( 45 ); eating behavior ( 46 ). Therefore, with the present study's findings, it is impossible to conclude with certainty that the Brainball program has a positive long-term impact on the development of physical fitness for second-grade students in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have previously demonstrated that the development of physical fitness is not only influenced by physical activities and sports, but also by factors such as genetics, environment ( 42 ); socioeconomic status of parents ( 43 , 44 ); parental education ( 45 ); eating behavior ( 46 ). Therefore, with the present study's findings, it is impossible to conclude with certainty that the Brainball program has a positive long-term impact on the development of physical fitness for second-grade students in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…20 The findings of this study are also supported by a previous study, which also found a significant relationship between parental education level and physical activity among adolescents, 21,22 especially in adolescents with obesity. 23 Falese et al (2021) explained that high physical activity levels among adolescents who have parents with high education levels because parents with high education are more likely to support youth involvement in physical activity, like choosing schools that can promote physical activity for their adolescents. 21 Galiano et al (2020) explained that highly educated parents have better knowledge about the benefits of physical activity for health, so they will spend time doing physical activity with their adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Parental education level also appears to be associated with the perception of barriers and facilitators to SB. One study [ 26 ] demonstrated that parents with a higher educational level engage more in PA with their children, compared to those with lower levels [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limiting TV time, causing children to spend more time playing outdoors, was associated with barriers [ 25 ]. In this sense, understanding SB in children and adolescents is an essential prevention strategy for public health [ 26 , 27 ], since SB is highly prevalent in the pediatric population and directly associated with the development of cardiometabolic diseases, which can lead to death in early adulthood [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%